Innovación en el sector cementero de Colombia: estudio de caso Cementos Tequendama (2015)
The aim of this work is to interpret the significance that Tequendama staff gives to innovation, taking the innovation model by the author Allan Afuah as a guide for the study, through the case study and in-depth interviews with key informants, represented by selected personnel in the company. The responses show that the main factors that the company has in mind when developing their innovation processes are the external and internal analysis, and the benefits obtained. The other components such as the analysis of impact and creation of value for different stakeholders, protection of innovation, and the role of the different players involved in the process, are not defined, or are carried out in a rudimentary form.